Variation for Grain Mineral Concentration in a Diversity Panel of Current and Historical Great Plains Hard Winter Wheat Germplasm. Issue 3 (1st May 2015) - Guttieri, Mary J.; Baenziger, P. Stephen; Frels, Katherine; Carver, Brett; Arnall, Brian; Waters, Brian M.
ABSTRACT: Wheat ( Triticum aestivum L.) grain mineral concentrations tend to decrease as yields increase, therefore, breeding for yield improvement may reduce wheat nutritional quality. The objectives of this study were to survey grain mineral concentration in Great Plains hard winter wheat to assess (i) the heritable variation for grain mineral concentrations in the germplasm pool, (ii) the effects of more than 50 yr of wheat breeding on mineral concentrations, and (iii) opportunities to exploit the underlying physiological relationship between grain protein concentration (GPC) and grain mineral concentration to improve nutritional quality. Grain mineral concentrations were measured in a panel of 299 winter wheat genotypes grown in 2012 and 2013 in Oklahoma and Nebraska. Cadmium and Li concentrations were most heritable across environments, and the low heritabilities of Fe and Zn concentrations will challenge direct breeding efforts, particularly within low‐yield environments that minimize genetic variance. Within the subset of cultivars released from 1960 to 2014, grain yield increased 0.58 to 1.25% yr −1, and Zn concentration decreased 0.15 to 0.26% yr −1, relative to the reference cultivar Scout 66. Grain concentrations of Fe, P, and S also trended lower over this time period. Significant genetic variation persists within contemporary germplasm. Among 93 cultivars released since 2000, Zn concentration max/min ratios ranged from 1.5 to 2.3, depending on environment. The positive interrelationship between GPC and grain Fe and Zn concentrations could be exploited in a yield‐neutral breeding strategy that selects genotypes based on positive grain protein deviation (GPD) in multiple environments.